The Role of Stakeholders in Masterplan Regeneration Decisions - Baker, HE; Moncaster, A (World Sustainable Built Environment Conference 2017 Hong Kong, 2017)
Brownfield sites often contain existing buildings and during regeneration the decision to demolish or adapt them should consider sustainability principles. This paper discusses decision-making criteria obtained through a literature review and primary research including 18 interviews, 2 workshops and 2 focus group discussions. The most frequently mentioned criteria including building condition; heritage value and capital costs are evaluated. Criteria are then analysed from different stakeholder perspectives and the paper identifies where stakeholder values align. The paper forms part of a three year research project which aims to develop a decision-making framework to assist with integrated and holistic decision making.
Keywords: urban regeneration; building adaptation; decision-making